2018
DOI: 10.1159/000492582
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk-Taking Behaviour and Brain-Derived Neurotrophic Factor Val66Met Polymorphism Correlates to Decreased Serum Brain-Derived Neurotrophic Factor Level in Heroin Users

Abstract: Background: This study has examined the relationships and interactions between serum brain-derived neurotrophic factor (BDNF) levels, BDNF Val66Met polymorphism and self-reported risk-taking behaviour in individuals with a history of heroin use undergoing outpatient treatment in comparison to healthy individuals. Methods: We enrolled 167 heroin users and 86 healthy subjects and examined serum BDNF levels, Val66Met polymorphism, and personal characteristics using Connor Davidson Resilience Scale, Risk-taking (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Although few causal genetic variants have been identified (Gelernter et al, 2014), the impact of these genetic aspects on the opioid dependence need to be determined. Serum BDNF levels were found to be significantly higher in Val/Val carriers than in Met/ Val or Met/Met in heroin users (Roviš et al, 2018). Besides, some prefrontal cortical areas are involved in the inhibition of nociception (Petrovic et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although few causal genetic variants have been identified (Gelernter et al, 2014), the impact of these genetic aspects on the opioid dependence need to be determined. Serum BDNF levels were found to be significantly higher in Val/Val carriers than in Met/ Val or Met/Met in heroin users (Roviš et al, 2018). Besides, some prefrontal cortical areas are involved in the inhibition of nociception (Petrovic et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to that, research by Zhang et al [ 20 ] found higher serum BDNF levels among heroin abusers than in controls. It is therefore worth mentioning that the genetic variant of BDNF ' Val66Met' was previously associated with decreased serum BDNF along with a self-reported risk-taking propensity among heroin users [ 37 ]. However, the BDNF 'Val68Met' polymorphism was found to increase compulsive alcohol drinking in mice [ 38 ], and the BDNF rs6265, rs11030104, and rs10767664 were reported to be associated with decreased heroin addiction risk [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substance use disorders (SUDs) have been particularly proliferative in investigating GxE with numerous reports of interactions between social adversity or stress exposure and genetic variants that influence risk of drug or alcohol abuse [36][37][38][39][40][41]. Chemical exposures-gene interactions that influence risk of psychiatric and neurologic diseases have also been reported.…”
Section: The Importance Of Including Genetics In Studies That Assess mentioning
confidence: 99%